Load-Strain Behaviour of Shredded Waste Paper Reinforced Concrete Beam - Solahuddin, Azuwa; Fadzil, Mat Yahaya (IOP Publishing, 2021)
Cement, sand, coarse aggregate, water and reinforcing bar are the materials to make a reinforced concrete beam. The waste paper has been dumped as waste and causes environmental pollution behind mill or landfill. The industry paper wastage for every year is increasing gradually. More spaces are being needed for landfills, uses energy loss of natural resources and increase of expenditure and various types of pollutions. Utilizing waste paper as an addition in concrete and reinforced concrete beam productions will reduce environmental pollutions. This research investigates the load-strain behaviour of reinforced concrete beam containing shredded waste paper using 10% copier and 10% cardboard waste paper as additions in the concrete mixture to the concrete shear strain and concrete bending strain of reinforced concrete beam. There are three types of beam shear reinforcements with stirrup spacing (SS)=100 mm, 150 mm, and 200 mm. All specimens are subjected to air curing at 28 days. The result of concrete bending and shear strains are higher by 10% shredded copier waste paper (SCPWP) and 10% shredded cardboard waste paper (SCBWP) with reducing shear reinforcements (SS=200 mm) and (SS=150 mm) compared to full shear reinforcement (SS=100 mm). This research shows that 10% SCPWP and 10% SCBWP improves the concrete bending and shear strains with reducing reinforcements. Furthermore, the results also show that 10% SCBWP has higher concrete bending and shear strains than 10% SCPWP for full and reduce shear reinforcements. This study indicates that shredded copier and cardboard waste paper can be used as additional materials in reinforced concrete beam production.